High gain 5G MIMO antenna for mobile base station - Yusnita Rahayu; Indah Permata Sari; Dara Incam Ramadhan; Razali Ngah (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This article presented a millimeter wave antenna which operated at 38 GHz for 5G mobile base station. The MIMO (Multiple Input Multiple Output) antenna consisted of 1x10 linear array configurations. The proposed antenna’s size was 88 x 98 mm^2  and printed on 1.575 mm-thick Rogers Duroid 5880 subsrate with dielectric constant of ε_r= 2.2 and loss tangent (tanδ) of 0.0009. The antenna array covered along the azimuth plane to provide the coverage to the users in omnidirection. The simulated results showed that the single element antenna had the reflection coefficient (S11) of -59 dB, less than -10 dB in the frequency range of 35.5 - 39.6 GHz. More than 4.1 GHz of impedance bandwidth was obtained. The gain of the antenna linear array was 17.8 dBi while the suppression of the side lobes was -2.7 dB.  It showed a high array gain throughout the impedance bandwidth with overall of VSWR were below 1.0646. It designed using CST microwave studio.